Analysis of the Alcohol Industry's Corporate Social Responsibility Practices in Portugal - Francisca Pulido Valente; Ana Carolina Baptista; Bárbara S. Vieira (Karger Publishers, 2024)
Introduction: In Portugal, the alcohol industry (AI) engages in corporate political activity, influencing decision-making and potentially obstructing the implementation of evidence-based alcohol policies, such as higher taxes, stricter advertising laws, and mandatory warning labels on all alcoholic beverages. Yet, no research has been conducted specifically on the industry's corporate social responsibility activities (CSR), which can also hinder the implementation of these cost-effective policies while serving as a means for nurturing its reputation. Methods: This study addresses this gap by examining the CSR practices of ten AI actors in Portugal. Through qualitative content analysis, data collected from their websites was categorized based on an adapted framework considering seven CSR categories. Results: The results revealed CSR practices across all categories, with corporate philanthropy and alcohol information provision and education accounting for 65% of the analyzed data. The findings highlight potential conflicts between the public health initiatives of AI in Portugal and its profit-driven objectives. Conclusion: CSR activities undermine health protection and alcohol harm prevention efforts by promoting a dubious discourse about an undeniably harmful substance. The present study recommends considering vigilant monitoring, regulation, or even the ban on CSR practices of AI in Portugal.